Does financial liberalisation improve access to investment finance in developing countries? - Conor M. O'Toole (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper considers the effect of financial liberalisation on access to investment finance using firm level data covering 57 developing and transition countries. An index is presented which measures financial market liberalisation along the following policy dimensions: directed lending, credit controls and reserve requirements, state control of banking,openness of international financial flows, banking market entry, prudential regulation and supervision, and securities market development. Categorising firms as financially constrained across four measures, the results indicate that financial liberalisation reduces the probability of being credit constrained, with the effect strongest for young, domestic private small and medium sized enterprises. Increases in the degree of liberalisation, decrease the probability of being constrained by between 5 and 20 percent depending on the constraint definition. However, for Sub-Saharan Africa, the results indicate that financial liberalisation actually increases financing constraints for firms. This may help explain the stylised fact that despite a commitment to financial reform, the predicted growth benefits have not been realised in this region.
Keywords: G00; F32; G32; 330; Financial liberalisation; access to credit : firm level investment; Finanzmarktregulierung; Investition; Unternehmensfinanzierung; Entwicklungsländer; Transformationsstaaten